Evaluation of the immune response of animals inoculated with serogroups A and C Neisseria meningitidis - Simonetti, José Pascoal (1976)
In order to study the immune response to serogroups A and C N. meningitidis the author inoculated 40 rabbits and 4 sheeps with live and dead bacteria as well as with specific A and C polysaccharides, with and without adjuvants in different doses and by different inoculation vias. SeveraI series of inoculation were carried out in order to verify the booster response. The leveI of the antibodies and their permanence in the serum was measured through passive haemagglutination and counter-immunoelectrophoresis. The same techinic was used to detect the polysaccharide antigens of N. meningitidis in these sera.The analysis of the results obtained indicated that there is no dífference in the immune responses at concentrations varying from 5,6 x 107 to 2,4 X 1010 bacteria per rabbit. Both haemagglutínatíng and precipitating antíbodíes appeared five days after the last inoculation and remamed for an average period of twenty five days. There was no significant differences between primary, secondary and tertiary responses yet the precipitating antibodies appeared in heavier concentrations after ínoculation of the sucessives series. When inoculated intravenously thepolisaccharides did not induoe immune response but they became ímmunogenic when injected intradermically whith complete Freund adjuvant.